Antiidiotypic antibodies to estradiol and gene polymorphisms of α and β estrogenic receptors in breast cancer patients - A. N. Glushkov; E. G. Polenok; L. A. Gordeeva; S. A. Mun; A. V. Antonov; P. V. Bayramov; N. E. Verzhbitskaya; G. I. Kolpinskiy; I. A. Vafin (Медицинская иммунология, 2024)
Markers for identification of ER+/PR breast cancer (BC) risks and conversion of ER+/ER+ to ER-/PR- tumors are necessary for effective prevention and therapy of BC by the selective ER – modificators. Purpose – To reveal the proposed associations of gene polymorphisms of   ESR1 and ESR2 and antiidiotypic antibodies to estradiol (IgG2-E2) with ER+/PR+ BC risk and conversion of ER+/PR+ to ER-/PR- tumors and to study the interrelations between gene variants of ESR and IgG2-E2 in healthy women and BC patients. Polymorphic loci of ESR1 (rs2234693) and ESR2 (rs4986938) were studied by the real time PCR in 370 healthy women and 1169 BC patients. Tumor tissues ER and PR were detected by the standard immunohistochemical methods. Serum IgG2-E2 were studied using non-competitive enzyme immuno-assay. TT, TC and CC genotypes of ESR1 were revealed with the equal frequency in healthy women and BC patients I stage. Homozygotes GG of ESR2 were detected rarely, but AA frequently in BC patients with ER+/PR+ tumors at the I stage, than in healthy women женщин (44.0% and 14.2% vs 52.7 and 8.4%, respectively; p=0.005). The low levels of IgG2-ES were revealed more rarely but high levels more frequently in BC patients with ER+/PR+ tumors at the I stage, that in healthy donors (39.8% and 60.2% vs 58.0% and 42.0%, respectively; p=0.0002). Decreasing of ER+/PR+ tumors proportion and corresponding increasing of ER-/PR- tumors from I stage to II–IV stages (71.7% to 58.9% and 13.9% to 23.1%; p=0.006) were revealed in TC heterozygotes of ESR1 only. The same conversion of ER+/PR+ tumors to ER-/PR- were detected in GG homozygotes of   ESR2 (p=0.004). There have been the similar ER/PR transformation in BC patients with high IgG2-E2 levels (74.7% to 57.6% and 11.3%, to 25.0%, respectively, p<0.0001). High and low IgG2-E2 levels were detected with the same proportions at the any genotypes of ESR1 and ESR2 in healthy women or in BC patients. ESR1-2 gene polymorphisms and serum IgG2-E2 levels may be used as independent markers for prediction of ER+/PR+ and for ER+/PR+ to ER-/PR- tumors conversion during BC progression.